Integrasi E-Servqual, Model Kano, dan HOQ dalam Meningkatkan Kepuasan Pelanggan Jasa Ojek Online - Wilson Kosasih; Iphov Kumala Sriwana; Rico Adhesi (Universitas Katolik Parahyangan, 2020)
Online motorcycle taxi service providers become business opportunities that grow and develop. The development of digital business opportunities is also supported by the increasingly widespread service users. This research aims to determine the characteristics of online motorcycle taxi service users and the attributes that are priority for users. In this study, several methods are used and integrated include: e-ServQual, IPA (importance-performance analysis), Kano Model, and House of Quality. The measurement result of the consumer satisfaction index is 55.58%, meaning that the consumers are quite satisfied with the online service. Based on the findings of this study, the attributes prioritized by consumers are the punctuality of the driver's arrival as stated in the application (attribute 14), the driver confirms the customer's order quickly (attribute 15), and the driver is easy to obtain (attribute 17). Finally, this study also recommends corrective actions to these service providers, among others: maintaining server reliability with a relative importance of 21.4%, regularly conducting driver training with a relative importance of 15.2%, and increasing the number of drivers with a relative importance 4.3%.